A comparative analysis on the adequacy of the computer crimes act 1997 in Malaysia and the computer misuse act 1990 in United Kingdom in governing the issue of phishing / Munira Masood...[et al.] - Masood, Munira; Ibrahim, Ikram; Kamar Rozaman, Khairul Aiman; Ahmad Khairy, Shazryll Aizad (2009)
The objective of this research is to determine the adequacy of the United Kingdom and the Malaysian laws in governing the issue of phishing. The computer related crime law that governs the issue of phishing in the United Kingdom is the Computer Misuse act 1990 while the Computer Crimes Act 1997 is applied in Malaysia. By analysing and comparing both of these Acts, the finding shows that both of these Acts are inadeqiate in governing the issue of phishing. To tackle this problem, the United Kingdom has enacted the Fraud Act 2006 which covers the real world as well as fraud in an online environment. Much earlier in 1998, the Malaysian government has created the Communications and Multimedia Act 1998 to govern the issue of phishing. The introduction of these two new legislations is said to be adequate in governing the issue of phishing. In addition to the legal measure in governing the issue of phishing the non-legal measures such as education and public awareness campaign as well as technologies involving two layer authentication and computer software program can be used to govern the issue of phishing.